Electrocatalytic oxygen evolution reaction (OER) on mixed nanoporous RuIr borides - Intikhab, Saad; Sokol, Maxim; Natu, Varun; Chatterjee, Swarnendu; Li, Yawei; Barsoum, Michel W.; Snyder, Joshua (Journal of applied electrochemistry, 2021)
Efficient water splitting for commercial electrolysis devices is predicated on the development of materials, specifically for the catalytic electrodes, that exhibit an optimal balance between activity and stability. Complicating the development of electrocatalytic materials, particularly for oxygen-evolving anodes in acidic polymer electrolyte membrane electrolyzers, is an inverse relationship between activity and stability. Here the development of a nanostructured oxygen evolution reaction (OER) electrocatalyst for low-pH water splitting is demonstrated. Dealloying of mixed RuIr borides is used to form a high aspect ratio electrocatalytic material that exhibits low OER overpotentials matching that of RuO x and electrolytic stability matching that of IrO x . Graphic abstract